2020
DOI: 10.1371/journal.pone.0238117
|View full text |Cite
|
Sign up to set email alerts
|

Temporal transcriptome analysis suggest modulation of multiple pathways and gene network involved in cell-cell interaction during early phase of high altitude exposure

Abstract: High altitude (HA) conditions induce several physiological and molecular changes, prevalent in individuals who are unexposed to this environment. Individuals exposed towards HA hypoxia yields physiological and molecular orchestration to maintain adequate tissue oxygen delivery and supply at altitude. This study aimed to understand the temporal changes at altitude of 4,111m. Physiological parameters and transcriptome study was conducted at high altitude day 3, 7, 14 and 21. We observed changes in differentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Increasing evidence shows that the harsh environment of hypoxia may regulate the immune system ( Mishra and Ganju, 2010 ; Gaur et al, 2020 ). In the present study, we found that the immune system of the spleen in gayal and yak was highly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence shows that the harsh environment of hypoxia may regulate the immune system ( Mishra and Ganju, 2010 ; Gaur et al, 2020 ). In the present study, we found that the immune system of the spleen in gayal and yak was highly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…GRIK2 (glutamate ionotropic receptor kainate type subunit 2) is a neurotransmitter receptor activated in a variety of normal neurophysiologic processes ( Sayers et al 2022 ) and acts as a thermoreceptor conferring sensitivity to cold temperatures ( The UniProt Consortium 2021 ). GRIK2 has been previously identified as a candidate gene associated with high-altitude adaptation in humans and other animals ( Ai et al 2014 ; Foll et al 2014 ; Gaur et al 2020 ). Together with ESR1 , these additional genes are possible candidate genes associated with high-altitude adaptation in Tibetan Partridges.…”
Section: Discussionmentioning
confidence: 99%
“…The blood plays a pivotal role in this response, primarily given its principal role as an oxygen carrier but also due to its other roles (e.g., coagulation, immune, and endocrine signaling). Few studies in the past investigated the blood transcriptional response to high altitude in humans ( Chen et al., 2012 ; Gaur et al., 2020 ; Liu et al., 2017 ). The current study has several important advantages compared with previous works.…”
Section: Discussionmentioning
confidence: 99%